Software Defined Radio, a perspective from education - Ramos, Mario Andrés; Camacho, Raul; Buitrago, Paola Andrea; Urda, Robert David; Restrepo, Julio Pastor (Frontiers in Education, 2024)
The evolution of communication systems has brought about a paradigm shift, particularly in radiocommunications, where software has increasingly taken precedence over hardware. This transition has not only reduced implementation costs but has also significantly enhanced the flexibility of equipment architecture. A prime example of this trend is the emergence and consolidation of Software Defined Radio (SDR) technology in recent decades. This paper provides a comprehensive contextualization of SDR technology, offering insights into its current state in terms of development tools and market equipment. Additionally, two learning scenarios are presented that employ different teaching methodologies. In one of these scenarios, communication theory is exclusively approached from a theoretical perspective. In the second scenario, knowledge acquisition is encouraged through the implementation of low-cost laboratories that incorporate SDR (Software-Defined Radio) technology. The study indicates that implementing SDR technology boosts student motivation and learning, with 73.13% believing it enhances engineering education and 96% showing increased motivation. Those using SDR in practical labs perform better on knowledge tests, but statistical analysis shows the difference is not statistically significant.